Intramolecular acylation of α-sulfinyl carbanion: a facile synthesis of (±)-pentenomycin I and (±)-epipentenomycin I. - Manat Pohmakotr (2018)
(±)-Pentenomycin I and (±)-epipentenomycin I were synthesized, starting from methyl 2,2-dimethyl-1,3-dioxolane-4-carboxylate. The key reaction involved the intramolecular acylation of α-sulfinyl carbanion and pyrolysis of the resulting product. © 1991.